Automated comparison system of the technical and economic efficiency of electric drives of crane mechanisms - Busher, Victor; Savich, Svetlana; Savich, Svyatoslav; Medvediev, Vadym (Eastern-European Journal of Enterprise Technologies, 2016)
Various types of the AC electric drive: traditional one with resistor control, with thyristor voltage converter and with frequency converter, the latter with power recovery are considered. The review of static and dynamic characteristics of each of the electric drives is presented, based on which recommendations are made concerning the application of a particular asynchronous electric drive of the proposed options in specific cases. Energy performance, loss in the motor circuits are calculated for specific crane hoist mechanisms. The CAD-system for technical and economic comparison of the crane drives taking into account the main operation features: loads, moments of inertia with/without load, the relative operating time with reduced speed is developed. Due to the unification of approaches to the analysis of the operating conditions of the hoist and swing mechanisms, the program calculates the power consumption in static and dynamic modes. Known capital and depreciation costs and total annual power losses obtained in the CAD-system allow making decisions about the choice or necessity of reconstruction of the electric drive.